Technology for the development of residual reserves by water-gas methods in conditions of associated petroleum gas shortage - Drozdov Alexander; Gorelkina Evgeniya (E3S Web of Conferences)
A method for injecting a water-gas mixture is proposed, which takes into account the distribution of reserves in a formation anisotropic in permeability. A schematic diagram of a device for pumping a mixture into a formation is presented. The proposed technology is based on obtaining a water-gas mixture with maximum gas content. This requires a device consisting of several pump-ejector systems. Booster pump-ejector systems pump a water-gas mixture saturated with oil gas into selected wells that open up significant volumes of residual reserves. In areas with small volumes of reserves, it is proposed to inject solutions of chemical reagents to release carbon dioxide in the formation. This solution will increase oil recovery by implementing the injection of the mixture in the most rational way and reduce damage from associated gas flaring. For greater efficiency of water-gas mixture injection, it is necessary to select the composition of the water-gas mixture (the composition of water and the injected gas), which helps to suppress the coalescence of gas bubbles in the conditions of the selected field. In order to clarify the injection parameters, it is recommended to conduct mineralization studies and studies of the settling rate of the water-gas mixture column depending on the composition of the injected gas.